(untitled) (Journal of human and social sciences, 2022)
Quality assurance in higher education has increasingly receiving a universal concern and been embraced in numerous educational institutions, especially in developed countries. However, this field has not experienced enough attention in developing countries, and therefore, very few researches conducted in this area. In Libyan higher education institution (LHEIs), the concept of quality assurance (QA) is still relatively new and LHEIs appear not adequately ready to implement QA. This research sets out to investigate the importance of using self-assessment practice as a technique for quality improvement in higher education (HE). It also investigates the influencing factors that may hinder or enhance the implementation of the self-evaluation process and how this process can improve the awareness of quality culture and the performance of the educational institution and thus encourage Libyan educational institutions to accelerate adopting this process.To achieve the objectives of this study a review of Arab and international literature for different academic experiments related to quality assurance in institutions of higher education. Through a review of previous literature on quality assurance in institutions of higher education. The results indicate that the self-assessment process can provide strong support and motivation to improve quality and performance efficiency as well as to promote awareness of quality culture and evaluation among the staff. Keywords: quality assurance, higher education, self assessment, quality culture